First do no harm: a real need to deprescribe in older patients. Issue 7 (6th October 2014) - Scott, Ian A; Anderson, Kristen; Freeman, Christopher R; Stowasser, Danielle A
Summary: Inappropriate polypharmacy in older patients imposes a significant burden of decreased physical functioning, increased risk of falls, delirium and other geriatric syndromes, hospital admissions and death. The single most important predictor of inappropriate prescribing and risk of adverse drug events in older patients is the number of prescribed medications. Deprescribing is the process of tapering or stopping drugs, with the goal of minimising polypharmacy and improving outcomes. Barriers to deprescribing include underappreciation of the scale of polypharmacy‐related harm by both patients and prescribers; multiple incentives to overprescribe; a narrow focus on lists of potentially inappropriate medications; reluctance of prescribers and patients to discontinue medication for fear of unfavourable sequelae; and uncertainty about effectiveness of strategies to reduce polypharmacy. Ways of countering such barriers comprise reframing the issue to one of highest quality patient‐centred care; openly discussing benefit–harm trade‐offs with patients and assessing their willingness to consider deprescribing; targeting patients according to highest risk of adverse drug events; targeting drugs more likely to be non‐beneficial; accessing field‐tested discontinuation regimens for specific drugs; fostering shared education and training in deprescribing among all members of the health care team; and undertaking deprescribing over an extended time frame under the supervision of a single generalist clinician.